Relasi Kekerabatan Bahasa Banjar dan Bahasa Bali: Tinjauan Lingusitik Histroris Kompratif - Jahdiah Jahdiah (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
It is comparative historical linguistic study that discuss the genetic relations of two languages in South Kalimantan, they are Bali and Banjar language. The problem of this study is 1) banjar dan Bali language that have same retensi, 2) Bnajar dan Bali language in the form of fonological innovation, 3) genetic relation of Bnajr and Bali language base on lexicostatistic calculation, 4) consonant and vocal correspondence, 5) consonant and vocal variation. The study aims relationship status of Bali and Banjar language through lexicostatistic calculation. The data are gained through interview by filling the questionaires consisting of 200 Swades vocabularies. Those vocabularies are classified into relationship and non relationship vocabularies. The theory which is used in this study is comparative historical linguistic theory. This study uses two approaches to determine and prove the close relationship of both languages, they are quantitative and qualitative approach. Lexicostatistic approach is used in quantitative approach, while comparation method is used in qualitative approach. The result shows that the relationship of Banjar and Bali language are in the grass level language. It is proven based on the calculation about 24,5%. This scale is proven by the same and similarity of both languages, they are 21 same vocabularies, 29 similar vocabularies of Banjar and Bali language. It can be conclude that Banjar and Bali language has close relationship.